Odpowiedzi

2009-11-25T17:45:46+01:00
A) (x+3)²=x²+6x+9
b) (3x+4)²=9x²+24x+16
c) (6y+2)²=36y²+24y+4
e) (0,2x+y)²=0,04x²+0,4xy+y²
f) (1,2a+1)²=1,44a²+2,4a+1
g) (2x+5y)²=4x²+20xy+25y²
1 5 1
2009-11-25T17:47:02+01:00
A) (x+3)²=x²+9+6x
b) (3x+4)²=9x²+16+24x
c) (6y+2)²=36y²+4+24y
e) (0,2x+y)²=0,04x²+y²+0,4xy
f) (1,2a+1)²=1,44a²+1+2,4a
g) (2x+5y)²=4x²+25y²+20xy
Najlepsza Odpowiedź!
2009-11-25T18:05:52+01:00
Wszystkie ze wzoru skr mnoz (a+b)²=a²+2ab+b²
mamy
a) (x+3)²=x²+2*3*x+3²=x²+6x+9
b) (3x+4)²=(3x)²+2*(3x)*4+4²=9x²+24x+16
c) (6y+2)²=36y²+24y+4
e) (0,2x+y)²=0,04x²+0,4xy+y²
f) (1,2a+1)²=1,44a²+2,4a+1
g) (2x+5y)²=4x²+20xy+25y²